Do You Just Discuss or Do You Solve?: Meeting Analysis in a Software Project at Early Stages - Klünder, Jil; Prenner, Nils; Windmann, Ann Kathrin; Stess, Marek; Nolting, Michael; Kortum, Fabian; Handke, Lisa; Schneider, Kurt; Kauffeld, Simone (Proceedings - 2020 IEEE/ACM 42nd International Conference on Software Engineering Workshops, ICSEW 2020, 2020)
Software development is a very cooperative and communicative task. In most software projects, meetings are a very important medium to share information. However, these meetings are often not as effective as expected. One big issue hindering productive and satisfying meetings is inappropriate behavior such as complaining. In particular, talking about problems without at least trying to solve them decreases motivation and mood of the team. Interaction analyses in meetings allow the assessment of appropriate and inappropriate behavior influencing the quality of a meeting. Derived from an established interaction analysis coding scheme in psychology, we present act4teams-short which allows real-time coding of meetings in software projects. We apply act4teams-short in an industrial case study at Volkswagen Commercial Vehicles, a large German company in the automotive domain. We analyze ten team-internal meetings at early project stages. Our results reveal difficulties due to missing project structure and the overall project goal. Furthermore, the team has an intrinsic interest in identifying problems and solving them, without any extrinsic input being required.
CRIS-Team Scopus Importer:2023-09-18
Keywords: Communication; development team; human factors; meetings; software projects